The Plasmid Replicon of Epstein-Barr Virus: Mechanistic Insights Into Efficient, Licensed, Extrachromosomal Replication in Human Cells - Lindner, Scott E. (2007)
The genome of Epstein-Barr Virus (EBV) and plasmid derivatives of it are among the most efficient extrachromosomal replicons in mammalian cells. The latent origin of plasmid replication (oriP), when supplied with the viral Epstein-Barr Nuclear Antigen 1 (EBNA1) in trans, provides efficient duplication, partitioning and maintenance of plasmids bearing it. In this review, we detail what is known about the viral cis and trans elements required for plasmid replication. In addition, we describe how the cellular factors that EBV usurps are used to complement the functions of the viral constituents. Finally, we propose a model for the sequential assembly of an EBNA1-dependent origin of DNA synthesis into a pre-Replicative Complex (pre-RC), which functions by making use only of cellular enzymatic activities to carry out the replication of the viral plasmid.